Resonant tunnelling in semiconductor heterostructures - Leadbeater, Mark Levence (1990)
This thesis examines the electrical transport properties of a series of n-type GaAs/(AIGa)As double barrier resonant tunnelling devices with well widths between 50 angstrem and 2400 angstrem . The current-voltage characteristics show peak-to-valley ratios as high as 25:1 and as many as seventy resonances, with clear evidence of quantum interference effects at room temperature. The application of a high magnetic field parallel to the current flow produces magnetooscillations in the transport properties which allow the sheet charge density in the accumulation layer to be determined. The energy level in the well over a wide range of bias is obtained from analysis of thermal activation of resonant tunnelling. The contributions of elastic scattering and LO phonon emission to the valley current are investigated spectroscopically with a magnetic field and two phonon modes of the (AIGa)As barrier are observed. The buildup of space charge in the quantum well at resonance leads to intrinsic bistability in the current and differential capacitance of an asymmetric structure. Magnetoquantum oscillations due to a degenerate electron gas in the well are used to measure this charge buildup and demonstrate that the tunnelling process is truly sequential. The bistability is dramatically enhanced at high magnetic fields when the lowest energy Landau level of the well can accommodate a high electron density. In a strongly asymmetric sample, a new kind of bistability is observed where the off-resonant current exceeds the resonant current due to enhancement of charge buildup by intersubband scattering. The modulation of the scattering rate by a magnetic field produces periodic oscillations in the width of the bistability. In a magnetic field applied perpendicular to the current, the resonances are broadened as a consequence of the conservation of canonical momentum. The transition from electric to magnetic quantisation in wide wells is investigated and tunnelling into interfacial Landau levels is observed. The angular dependence of the resonances is used to probe conduction band anisotropy. In a tilted field, a completely new type of magneto-oscillations is observed.